Social competence of physicians and medical students – a preliminary report - Mroczek, Bożena; Zarek, Aleksandra; Rudnicki, Jacek; Wolińska, Weronika; Pawlak, Iwona; Dyk, Tadeusz; Kotwas, Artur; Kurpas, Donata (Family Medicine & Primary Care Review, 2016)
Background . Efficient functioning at work and in the environment depends on social and emotional competence, understood as complex skills that determine the effectiveness of behaviors in various professional and social situations. Objectives. The aim of this study was to determine the social competence of physicians and medical students with regard to the sociodemographic contributors which shape social competence. Material and methods . The study was conducted in 2015 and 2016 and it involved 90 physicians, including 25 GPs (27.8%) and 53 medical students of PMU in Szczecin. The median age of the physicians and the students was 32 and 25, respectively. The Social Competencies Questionnaire (SC Q) by Anna Matczak and a self-developed survey questionnaire were employed. Results. The ability of physicians to achieve medium and high levels of social competence increases by 8.5% with every year of seniority. Membership in scientific societies increases the odds of a high level of social competence fivefold in the ES scale and fourfold in the A scale. Physicians involved in the education of medical students were less likely to obtain medium and high scores (5 stens) in the A scale. An increase in seniority in the last workplace is accompanied by a 0.93 times lower probability of obtaining a high competence score in the A scale. Similarly, third cycle degree studies increase the odds of achieving high competence level by 7.48 times in the A scale. Conclusions . Low levels of competence can be expected from physicians with less seniority, not belonging to scientific societies, not involved in students’ education, working in only one place, and not participating in third cycle degree studies. This group should be provided with social competence training.